Product quality, productive efficiency, and international technology diffusion : evidence from plant-level panel data - Kraay, Aart 1995- (Policy research working paper, 2002)
In Colombia, Mexico, and Morocco, firms' past exposure to foreign knowledge through exports, imported imputs, and foreign direct investment does not help to predict current product quality or productive efficiency